Pembuatan Standar Operasional Prosedur (SOP) Praktikum Untuk Meningkatkan Efesiensi Pelasanaan Pratikum Fisika SMA - Handayani, Sri; Suseno, Nyoto; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2020)
ABSTRACTThe problem in this research is that the management of the physics laboratory is still not optimal. Therefore, it is necessary to have a managementsystem or management of laboratory implementation in a good physics laboratoryby creating standard operating procedures (SOP) for practicum implementation. The aim to be achieved in this study is to produce an SOP for practicum implementation in the utilization of physics laboratories in senior high school and to determine the efficiency of the implementation of senior high school physics practicum after using the developed SOP. The development model used in this research is the ADDIE development model, which is an extension of Analysis, Design, Development, Implementation, and Evaluation. The product feasibility level is seen from the results of validation from laboratory management experts, the results of the feasibility percentage of practicum SOP are 83.33%, and the percentage of students' responses obtained from the product trial results is91.38%. Thus, it can be concluded that the practicum SOP developed is suitable for use in the process of practical activities. Keywords: standard operational procedure, efficiency, and practicum.